Seepage effects on settling velocity - Lee, Leon Xu Heng (2016)
Settling is the process whereby the particles settle to the bottom of a fluid and thereby forming a sediment. These particles experience a force, either by gravity or centrifugal motion and they tend to move in the direction of the force. Particles that settle because of gravity tends to fall to the bottom of the containment forming a fluid mixture of solid and liquid at the base of the containment. Settling effect of particles holds a great importance in many engineering fields and processes such as wastewater treatment where sedimentation, coagulation and flocculation are important processes. This experiment aims to investigate the effect of downward seepage on settling velocity of sediment particles using spheres as the experimental tool through experimentation, observation and calculation. The experiments are conducted in a vertical water cylinder where the spheres of different diameter (0.0984cm, 0.1362cm, 0.1716cm, 0.2364cm) and weight under an increasing downward seepage outflow rates (2.156 x 10-5m^3/s , 2.380 x 10-5 m^3/s , 2.939 x 10-5 m^3/s , 4.208 x 10-5 m^3/s ). The drag coefficient of the particles holds significant importance as it shows the resistance of an object in a fluid medium and during the experiment, drag coefficient of the spheres are compared to previous predecessors results which to ensure accuracy and similarity of spheres. Though there were several downward seepage flowrates that showed an increase settling velocity of spheres, there is insignificant evidence to relate down seepage and the increased settling velocities as the other flowrates relating to settling velocities showed slower or similar results to settling velocities under quiescent condition. The hypothetical zone for seepage acceleration under downward seepage influence remains insignificant.